Proses Diseminasi Informasi Tentang Pemilihan Kepala Daerah (Pilkada) Kota Padang Tahun 2018 Dalam Rangka Meningkatkan Partisipasi Pemilih - Ilham Firdaus; Asmawi Asmawi; Asrinaldi Asrinaldi (IAI Darussalam, 2019)
This research describes and analyzes the communication model carried out in the implementation of the process of disseminating the election of the Regional Head (Pilkada) of the City of Padang in 2018 in order to increase voter participation. This study uses the concept of excellence theory according to Grunig and Hunt, were in increasing voter participation in regional elections can be seen from various models, namely first: the press agentry model Second: public information Third: two way asymmetric and fourth: two way symmetric. This research uses the post-positivism research paradigm with qualitative methods and the type of case study approach. The process of data collection is done through interviews and documentation. The results showed that election dissemination carried out by one-way method, media, and face-to-face with emphasis on dialogue as a model of communication conducted turned out to be able to deliver messages to the effect to the community. Therefore, the message of the election delivered uses a cultural approach that was built by prioritizing face-to-face and media as an effort to increase community participation in regional elections.